2007
DOI: 10.1017/s000711450770497x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three different conjugated linoleic acid preparations on insulin signalling, fat oxidation and mitochondrial function in rats fed a high-fat diet

Abstract: To investigate the effects of three different conjugated linoleic acid (CLA) preparations containing different ratios of CLA isomers on insulin signalling, fatty acid oxidation and mitochondrial function, Sprague -Dawley rats were fed a high-fat diet either unsupplemented or supplemented with one of three CLA preparations at 1 % of the diet for 8 weeks. The first CLA preparation contained approximately 30 % cis-9, trans-11 (c9,t11)-CLA isomer and 40 % trans-10, cis-12 (t10,c12)-CLA isomer (CLA-mix). The other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 56 publications
2
27
3
2
Order By: Relevance
“…However, in contrast to our results, various authors demonstrated a beneficial effect of CLA on glucose uptake and glycogen synthesis in the presence of insulin in obese-diabetic rats [4,35]. These effects were associated with an increase in adiponectin levels, which reduced the IRS-1 phosphorylation in serine residues, thus resulting in decreased insulin resistance [44,45]. Furthermore, the improvement in insulin sensitivity observed in mice supplemented with CLA has been previously related to the peroxisome proliferator-activated receptor α and γ levels in response to long-term but not short-term treatments [5].…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast to our results, various authors demonstrated a beneficial effect of CLA on glucose uptake and glycogen synthesis in the presence of insulin in obese-diabetic rats [4,35]. These effects were associated with an increase in adiponectin levels, which reduced the IRS-1 phosphorylation in serine residues, thus resulting in decreased insulin resistance [44,45]. Furthermore, the improvement in insulin sensitivity observed in mice supplemented with CLA has been previously related to the peroxisome proliferator-activated receptor α and γ levels in response to long-term but not short-term treatments [5].…”
Section: Discussioncontrasting
confidence: 99%
“…Oxidative stress, in addition to its causal role in the upregulation of proinfl ammatory cytokine and hepatocellular injury markers (higher ALT and GGT), plays a central role in the transition from steatosis to NASH and represents a characteristic sign of animal ( 42 ) and human NA-FLD ( 43 ). Data showing the protective effects displayed by CLA administration to L-fed rats agree with the recently reported ability of CLA to improve liver status activity ( 17 ), Supplemental Material can be found at: may be hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of a HFD feeding and the lipid contents and type of the diets lead to alterations in the degree of insulin resistance and in the lipid metabolic parameters (Choi et al 2007). The results of the present study revealed that feeding HFD to C57BL/6J mice for ten weeks could develop metabolic abnormalities including overweight, hyperglycemia, dyslipidemia, hyperinsulinemia, insulin resistance and hypertension.…”
Section: Discussionmentioning
confidence: 99%